El uso del material didáctico y el proceso de enseñanza – aprendizaje de biología en los estudiantes del primer año común del colegio nacional nocturno “Catamayo” de la provincia de Loja, cantón Catamayo, parroquia Catamayo, período lectivo 2010 – 2011.” Lineamientos propositivos - Cumbicus Bravo, Anita Lucía (2014)
The training material is to be mediating the methodological process of teaching resources - learning because they are used in the educational planning of teaching, help set the goals outlined in the class, and favor the reconstruction of knowledge and the cultural meanings of curriculum on students. This research work entitled to " The Use of Learning Materials and Teaching Process - Learning Biology in Common First Year Students of the National College Night " Catamayo " De Loja Province Region Catamayo Catamayo Parish , Period school 2010 - 2011 . " That is why the overall objective of this research work is to contribute to the use of Learning Materials in the improvement of the teaching - learning content Osteology, Myology Arthrology and that are taught in the subject of Biology in the Common First Year students of the National College Night " Catamayo " , in order to enhance the educational process of the institution. This research is descriptive, analytical, explanatory and purposeful character, since the variables described investigate very important in the development of research, also the study of the teaching materials used by the teacher was made, which constitutes a mediator resource and enhancing the teaching - learning process. The methods used in the development of this investigation were: scientific, inductive, deductive, descriptive and analytical method method - synthetic, since they allowed for discussion and comparison of the proposed variables. Also techniques and instruments as survey that was applied to 6 teachers Area of Natural Sciences and 150 students in parallel "A" "B" "C" and "D" of the first Common Year Night National College "were used Catamayo "in order to know what kind of strategies are applied in the development of the Teaching - Learning of Biology; to determine whether the strategies used, allow learning what studied. In addition, these tools allow to determine the predisposition of the investigated regarding the proposal. From the results obtained from the application of these surveys , it was determined that 83 % of teachers used as the main teaching resource guide texts and permanent material comprised in the draft, and whiteboard markers ; practical content of the course Biology limiting learning learners - from the above, this material does not establish the theoretical link is concluded . The institution does not have a bio lab adequately equipped, but it has a computer lab. That is why the group of researchers proposes: Educational software as an alternative proposal to the work of the subject of biology regarding the contents of Arthrology , Osteology and Myology in the Common First Year Night National College Catamayo during the academic year 2010 - 2011 as a way of including ICT ` s development of the Teaching - learning of said subject , taking into account the suggestions of the new curriculum based on active learning methodology